Portal-systemic encephalopathy with hypermanganesemia: A case report and review of the literature - İ. Safa Yıldırım (Dicle Medical Journal, 2012)
Hepatic encephalopathy (HE) is a neuropsychiatric syndromeof patients with chronic liver disease. In addition toammonia levels, increased manganese levels in the brainare also considered as having role in the pathogenesisof HE. On cranial T1-weighted magnetic resonance imaging(MRI), hyperintense and symmetrical globus pallidilinked to the manganese deposition are characteristicfor patients with cirrhosis of the liver. We presented herea case of portal-systemic encephalopathy demonstratedwith typical MR images and increased blood manganeseconcentration.